Tip cell-specific requirement for an atypical Gpr124- and Reck-dependent Wnt/β-catenin pathway during brain angiogenesis - Vanhollebeke, Benoit (eLife, 2015)
Despite the critical role of endothelial Wnt/β-catenin signaling during central nervous system (CNS) vascularization, how endothelial cells sense and respond to specific Wnt ligands and what aspects of the multistep process of intra-cerebral blood vessel morphogenesis are controlled by these angiogenic signals remain poorly understood. We addressed these questions at single-cell resolution in zebrafish embryos. We identify the GPI-anchored MMP inhibitor Reck and the adhesion GPCR Gpr124 as integral components of a Wnt7a/Wnt7b-specific signaling complex required for brain angiogenesis and dorsal root ganglia neurogenesis. We further show that this atypical Wnt/β-catenin signaling pathway selectively controls endothelial tip cell function and hence, that mosaic restoration of single wild-type tip cells in Wnt/β-catenin-deficient perineural vessels is sufficient to initiate the formation of CNS vessels. Our results identify molecular determinants of ligand specificity of Wnt/β-catenin signaling and provide evidence for organ-specific control of vascular invasion through tight modulation of tip cell function. DOI: http://dx.doi.org/10.7554/eLife.06489.001